Malaysia’s current account deficits : an intertemporal optimization perspective. - Ismail, Hamizun; Baharumshah, Ahmad Zubaidi (Springer Verlag, 2008)
The study examines the account imbalances in Malaysia during the past four decades. Using Sachs’s (National Bureau of Economic Research,Working Paper No. 859, 1982) intertemporal model, we address the issue of external solvency by measuring the deviation of actual from the optimal path of the current account balance. All in all, we found that the actual path moves reasonably close to the estimated consumption-smooth currents accounts, suggesting that the current account balances satisfy the external solvency condition. The major findings from the empirical application of the model revealed the following: (i) the deficits of the 1990s prior to 1997 financial crisis were sustainable; (ii) the evidence appears to suggest that the current account balance broadly follows the same pattern of the intertemporal model and hence suggests that capital ismobile; (iii) the large surpluses observed during the post-1997 period significantly deviate from the optimal path, implying that consumption is unsustainable and is expected to fall in the near future and; (iv) there is excessive volatility in international capital movements for consumption-smoothing purpose.